2015
DOI: 10.1007/s13580-015-0136-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of tree-based water status indicators at the onset of water deficit in citrus

Abstract: This experiment evaluates the potential of using parameters based on tree trunk fluctuations for detecting water deficit in citrus trees under two different water saving-irrigation strategies: sustained deficit irrigation and partial root-zone drying. Three irrigation treatments were applied: 1) Control: trees were irrigated with 100% of their evapotranspirative needs (ETc); 2) 60 sustained deficit irrigation (SDI): 60% ETc; and 3) partial root-zone drying (PRD): 100% ETc needs, applied to only one-half of roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In contrast, Martín-Palomo [111] concluded that MDS was not a useful indicator for irrigation scheduling in almonds because of the great trunk growth, suggesting the tree growth rate as a more sensitive stress indicator. In citrus [180] and avocado [105], it was found that absolute MDS values show large day-to-day variations due to the variable environmental conditions. Elsayed-Farag and Melgar [180] suggested the use of the MDS ratio in automatic irrigation scheduling, while the authors of ref.…”
Section: Stem Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Martín-Palomo [111] concluded that MDS was not a useful indicator for irrigation scheduling in almonds because of the great trunk growth, suggesting the tree growth rate as a more sensitive stress indicator. In citrus [180] and avocado [105], it was found that absolute MDS values show large day-to-day variations due to the variable environmental conditions. Elsayed-Farag and Melgar [180] suggested the use of the MDS ratio in automatic irrigation scheduling, while the authors of ref.…”
Section: Stem Diametermentioning
confidence: 99%
“…In citrus [180] and avocado [105], it was found that absolute MDS values show large day-to-day variations due to the variable environmental conditions. Elsayed-Farag and Melgar [180] suggested the use of the MDS ratio in automatic irrigation scheduling, while the authors of ref. [105] concluded that the evaluation of the impacts of the various local phenological and environmental factors is crucial since MDV represents water stress history rather than actual PWS.…”
Section: Stem Diametermentioning
confidence: 99%